Design and validation of Iranian Child Health-Friendly Neighbourhood checklist: a mixed-methods study - Ali Ramezankhani; Parisa Akhbari; Nastaran Keshavarz Mohammadi; Farid Zayeri; Pantea Hakimian; Nasrin Sahamkhadam (BMJ Publishing Group, 2024)
Background A child health-friendly neighbourhood is defined as a neighbourhood where the child's health is provided, protected and promoted. Designing and validation of an assessment tool is required to identify the deficits and strengths of neighbourhoods within the context of each country. This study aimed to design and validate a child health-friendly neighbourhood assessment tool in Tehran.Methods A mixed-methods approach using semistructured interviews with 31 participants (15 mothers of children under 6 years old and 16 experts) conducted in Tehran between 2021 and 2022. Face validity, content validity and reliability of the checklist were calculated. Highly influenced by the Child Friendly City framework, designing and validation of the checklist was carried out through three phases: (a) identifying the child health-friendly neighbourhood domains and subdomains, (b) drafting the Iranian Child Health-Friendly Neighbourhood checklist and (c) validation of the designed checklist.Results Following three phases of study, the final version of the checklist consisted of six dimensions, namely green space and park, recreational centre, passage and street, healthcare centre, cultural centre and kindergarten. Each dimension encompassed five domains of facilities and services, accessibility, security, safety and aesthetics and view, with 42 indicators, 77 subindicators and 273 items.Conclusions The child health-friendly neighbourhood checklist has a more health focus on neighbourhood level and is more contextually specific, relevant and appropriate compared with UNICEF's Child Friendly City framework. It also showed acceptable validity and reliability; therefore, the checklist could be a feasible tool to assess child health-friendly neighbourhoods.